2018
DOI: 10.1007/978-3-030-00928-1_60
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Matching Losses Can Hallucinate Features in Medical Image Translation

Abstract: This paper discusses how distribution matching losses, such as those used in CycleGAN, when used to synthesize medical images can lead to mis-diagnosis of medical conditions. It seems appealing to use these new image synthesis methods for translating images from a source to a target domain because they can produce high quality images and some even do not require paired data. However, the basis of how these image translation models work is through matching the translation output to the distribution of the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(180 citation statements)
references
References 10 publications
3
177
0
Order By: Relevance
“…In fact, cycle-GANbased methods have been shown to be limited in their ability to transform images even from one MR to a different MR sequence. 7 This approach overcomes the limitations of the prior approaches by incorporating structure-specific losses that constrain the cross-modality transformations to preserve atypical structures including tumors. We note however that all of these methods produce pseudo MR representations that do not create synthetic MR images modeling the same tissue specific intensities as the original MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, cycle-GANbased methods have been shown to be limited in their ability to transform images even from one MR to a different MR sequence. 7 This approach overcomes the limitations of the prior approaches by incorporating structure-specific losses that constrain the cross-modality transformations to preserve atypical structures including tumors. We note however that all of these methods produce pseudo MR representations that do not create synthetic MR images modeling the same tissue specific intensities as the original MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Additional testing was performed on a total of 39 MRI scans obtained from 22 patients who were not used in training or validation. Three of those patients contained longitudinal MRI scans (7,7,6). Table II contains details of the numbers of analyzed scans, patients, and ROIs (256 9 256) used in training and testing.…”
Section: E Implementation and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…One difficulty with this approach is to ensure that the learned transformations sufficiently translate style while (1) remaining realistic, and (2) preserving content (anatomy) such that they are label-preserving [37]. As noted by Cohen et al [38], this is particularly problematic when using approaches based on adversarial losses (e.g. CycleGAN [34]) which aim to match the translation output with the distribution of the target domain, commonly introducing anatomical artifacts into the translated output, and introducing inconsistencies between the input labels and the transformed outputs.…”
Section: Discussionmentioning
confidence: 99%
“…However, if proper care is not taken to represent truthfully the distribution of the data (e.g., not including enough tumor samples in a harmonization task between datasets with pathological data), this can lead to severe issues. Cohen et al (2018) recently showed that in such a case, GAN based methods could try to remove the pathology in the data to match the distribution of healthy subjects that the method previously learned, precluding potential applications to new datasets or pathological cases not represented "well enough" in the training set. The same concept would likely apply to systematic artifacts; if every dataset from a target scanner is corrupted by, e.g., a table vibration artifact, it may very well be possible that a harmonization algorithm will try to imprint this artifact to the source datasets to match the target datasets.…”
Section: Limitationsmentioning
confidence: 99%